Role of behavioral biases in the investment decisions of Pakistan Stock Exchange investors: Moderating role of investment experience - Saima Aziz; Shahid Mehmood; Muhammad Asif Khan; Anita Tangl (Investment Management & Financial Innovations, 2024)
Despite many revolutionary asset pricing models developed over the past decades, traditional finance does not explain investor behavior very well. The purpose of this study is to examine the influence of behavioral biases on the investment decisions of investors of Pakistan Stock Exchange. In addition, the moderating influence of investment experience investigated in this study. The findings were reported using a sample of 230 individual investors, who make their own investments, typically through a mutual fund, bank, or internet broker. They make investments to achieve their unique investment objectives, such as saving for retirement, a child’s education, or increasing their overall wealth. The influence of behavioral biases on investment decisions was calculated using regression analysis. Regression results show that beta and t-values are significant and have a significant impact on investment decisions. Regression findings show that Confirmation Bias, Gamblers Fallacy Bias, Negativity Bias, Bandwagon Effect Bias, Loss Aversion Bias, and Overconfidence Bias all have a substantial impact on Investment Decisions. Status quo prejudice and endowment bias have a favorable but minor influence on Investment Decisions. Investment Experience is regarded as an essential component that contributes to successful decision making under risk and uncertainty, however the results of this study show that moderating variables have a minor influence. According to the findings, the moderating variable had no effect on the connection between behavioral biases and investment decisions. And the reason for this is that behavioral biases persist regardless of investing experience.